Factors Inhibiting Entrepreneurship in Fashion Students - Laila Nurul Himmah; Chytra Mahanani (Yayasan Pendidikan dan Pengembangan Harapan Ananda, 2026)
Fashion student entrepreneurship has an important for the growth of the creative industry and the regional economy. However, limited evidence exists regarding the specific barriers faced by fashion students in vocational higher education in Indonesia. This study aims to identify the dominant entrepreneurial barriers among students of the Fashion Study Program at UNY. A quantitative descriptive approach was employed using an online questionnaire administered to 41 students selected through purposive sampling. Instrument quality was confirmed by validity testing, with all items meeting the required criteria, and reliability testing, which showed acceptable internal consistency (Cronbach's Alpha = 0.715). Descriptive analysis revealed that limited business capital (M = 3.5) was the primary barrier, followed by limited access to production technology (M = 3.4), limited business networks and support (M = 3.3), and market competition (M = 3.0). The novelty of this study lies in providing an empirical description of entrepreneurial barriers specific to fashion students within the context of vocational education. The findings contribute to entrepreneurship education by offering evidence to support the development of targeted institutional strategies. Universities should strengthen the entrepreneurial ecosystem by improving access to funding, production facilities, business mentoring, and industry collaboration to better prepare students for sustainable entrepreneurial careers.